Antimicrobial Activity of Ceftriaxone Compared with Cefotaxime in the Presence of Serum Albumin. (1995) - Nath, Swapan K; Foster, Gary A; Mandell, Lionel A; Rotstein, Coleman
Abstract : The effect of serum albumin on the antimicrobial activity of ceftriaxone, cefotaxime, and a 1:1 ratio of cefotaxime and its desacetyl metabolite against nonpseudomonal Gram-negative bacilli was determined. Antimicrobial activity of drugs was evaluated by measuring minimum inhibitory (mic ) and bactericidal (mbc ) concentrations in broth with and without human serum albumin. The analysis of logarithmically transformed mean mic s and mbc s showed that there was a highly significant interaction between drug and serum albumin (P<0.0001). The inhibitory and bactericidal activities were greatest for cefotaxime followed by cefotaxime/desacetylcefotaxime and ceftriaxone (P<0.01). Time-kill kinetics demonstrated that ceftriaxone was less bactericidal than cefotaxime in broth with albumin. On the basis of these results it was concluded that the in vitro antimicrobial activity of ceftriaxone compared with that of cefotaxime was significantly diminished in the presence of serum albumin.